From Stressful Experiences to Depression in Chinese Migrant Children: The Roles of Stress Mindset and Coping - Chen, Luxi; Qu, Li (Frontiers in Psychology, 2021)
Migrant children are at high risk for depression, though the exact mechanism is still unclear. This study investigated whether and how different stress mindsets (threat vs. challenge) and coping strategies (avoidant vs. approach) mediated the association between stressful experiences and depression in migrant children, and whether these relationships would be moderated by gender. One hundred and ninety-eight rural-to-urban migrant children (56.0% girls; Mage = 11.8 years; Range: 9-15) in Beijing, China, completed self-administered measures of stressful experiences, threat- and challenge-mindsets, coping strategies and depression. Path analysis was conducted to examine the proposed mediation model. A dual-pathway model of stress coping was discovered: (1) a stress-threat-avoidant-depression pathway, in which threat-mindset and avoidant coping mediated the association between stressful experiences and depression, and (2) a challenge-approach-enhancement pathway, in which approach coping mediated the association between challenge-mindset and fewer depressive symptoms, without being influenced by stressful experiences. Despite the greater vulnerability of girls to depression, negative life events, negative stress mindset and maladaptive coping strategies, the dual-pathway mechanism was not moderated by gender, indicating that the pathways to depression did not vary by gender. Together, findings suggest that stressful events, threat-mindset and avoidant coping act as risk factors for depression, whereas challenge-mindset and approach coping can function as protective factors to counteract the impacts of stressful experiences and promote psychological well-being among migrant children.